Taxonomy of the ant genus Nesomyrmex Wheeler (Formicidae, Myrmicinae) in the Afrotropical region, with a review of current species groups and description of a new species of the N. angulatus group from Mozambique - Hita Garcia, Francisco; Mbanyana, Nokuthula; Audisio, Tracy Lynn; Alpert, Gary D. (European Journal of Taxonomy, 2017)
This study reviews the taxonomy of the ant genus Nesomyrmex Wheeler, 1910 in the Afrotropical region. Previous revisionary studies are discussed and four species groups are proposed on the basis of external morphology. The N. angulatus group contains seven species that are widely distributed throughout the whole Afrotropical region, with one species also occurring in the Palaearctic and Malagasy regions. The N. cataulacoides group is monotypic, with one morphologically bizarre species found in Equatorial rain forests. The N. humerosus group is also monotypic and occurs in East Africa. The last and by far most species-rich group is the N. simoni group that contains 17 species, all of which are endemic to South Africa. The four groups are defined for the first time for the region, and an illustrated identification key is provided. Furthermore, the N. angulatus group is more thoroughly reviewed. One new species from Mozambique is described, N. inhaca sp. nov., and species accounts for the other six are provided. Also, an illustrated identification key to the species of the N. angulatus group is presented.